Effect of Nano and Micro Friction Modifier Based Lubricants on Wear behavior between Steel-Steel Contacts - S. Bhaumik; S.D. Pathak (Tribology in Industry, 2017)
The wear and surface morphology between steel (EN24, 22-24Rc)-steel (EN 31, 58-60Rc) contacts was investigated in presence of friction modifiers based (micro-graphite/nano particles- multi wall carbon nano tubes and zinc oxide) mineral oil. Though a decrease in wear was observed (upto a certain concentration of nano friction modifiers) but a weight-gain in pins after the tests was observed for all tests with ZnO nanoparticles while weight loss was observed in tests with multi wall carbon nano tubes and graphite particles based oil samples. Surface characterization of the worn surfaces showed more surface deteriorations in case of mineral oil (no friction modifiers) and mineral oil with graphite as compared with nano particles/tubes based lubricants. The occurrence of a tribo film due to the deposition of nano particle and the formation of a modified layer on the pin surfaces are likely to be responsible for the reduction of coefficient of friction and better surface roughness. Apart from investigating the wear behaviour between two steel surfaces under micro and nano particles based lubricant and analysing the surfaces of the samples a part of the work was also focussed on the weight gain after tribo tests with ZnO nano particle additions.